Acute impact of conventional and Eccentric cycling on platelet and vascular function in patients with chronic heart failure - Haynes, A.; Linden, M.; Chasland, L.; Nosaka, K.; Maiorana, Andrew; Dawson, E.; Dembo, L.; Naylor, L.; Green, D. (The American Physiological Society, 2017)
Evidence-based guidelines recommend exercise therapy for patients with chronic heart failure (CHF). Such patients have increased atherothrombotic risk. Exercise can transiently increase platelet activation and reactivity and decrease vascular function in healthy participants, although data in CHF are scant. Eccentric (ECC) cycling is a novel exercise modality that may be particularly suited to patients with CHF, but the acute impacts of ECC cycling on platelet and vascular function are currently unknown. Our null hypothesis was that ECC and concentric (CON) cycling, performed at matched external workloads, would not induce changes in platelet or vascular function in patients with CHF. Eleven patients with heart failure with reduced ejection fraction (HFrEF) took part in discrete bouts of ECC and CON cycling. Before and immediately after exercise, vascular function was assessed by measuring diameter and flow-mediated dilation (FMD) of the brachial artery. Platelet function was measured by the flow cytometric determination of glycoprotein IIb/IIIa activation and granule exocytosis in the presence and absence of platelet agonists. ECC cycling increased baseline artery diameter (pre: 4.0?±?0.8 mm vs. post: 4.2?±?0.7 mm; P = 0.04) and decreased FMD%. When changes in baseline artery diameter were accounted for, the decrease in FMD post-ECC cycling was no longer significant. No changes were apparent after CON. Neither ECC nor CON cycling resulted in changes to any platelet-function measures (all P > 0.05). These results suggest that both ECC and CON cycling, at a moderate intensity and short duration, can be performed by patients with HFrEF without detrimental impacts on vascular or platelet function.NEW & NOTEWORTHY This is the first evidence to indicate that eccentric (ECC) cycling can be performed relatively safely by patients with chronic heart failure (CHF), as it did not result in impaired vascular or platelet function compared with conventional cycling. This is important, as acute exercise can transiently increase atherothrombotic risk, and ECC cycling is a novel exercise modality that may be particularly suited to patients with CHF.